Control of mixed convection in lid-driven enclosures using conductive triangular fins - Sun, Changzheng; Yu, Bo; Öztop, Hakan Fehmi; Wang, Yi; Wei, Jinjia (Pergamon-Elsevier Science Ltd, 2011)
Control of mixed convection (combined forced and natural convection) in a lid-driven square cavity is performed using a short triangular conductive fin. A numerical technique is used to simulate the flow and temperature fields. The vertical walls of the cavity are differentially heated. Both the top lid and the bottom wall are adiabatic. The fin is located on one of the motionless walls of the cavity. Three different cases have been studied based on the location of the fin. In this context, Cases I, II and III refer to the fin on the left, bottom and right walls, respectively. Results are presented for +x and -x directions of the top lid in horizontal axis and different Richardson numbers as Ri = 0.1, 1.0 and 10.0. It is observed that the triangular fin is a good control parameter for heat transfer, temperature distribution and flow field. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Mixed convection; Lid-driven cavity; Triangular fin